Serum Procalcitonin as a Useful Serologic Marker for Differential Diagnosis between Acute Gouty Attack and Bacterial Infection - Choi, Sang Tae; Song, Jung-Soo (Yonsei medical journal, 2016)
Patients with gout are similar to those with bacterial infection in terms of the nature of inflammation. Herein we compared the differences in procalcitonin (PCT) levels between these two inflammatory conditions and evaluated the ability of serum PCT to function as a clinical marker for differential diagnosis between acute gouty attack and bacterial infection. Serum samples were obtained from 67 patients with acute gouty arthritis and 90 age-matched patients with bacterial infection. Serum PCT levels were measured with an enzyme-linked fluorescent assay. Serum PCT levels in patients with acute gouty arthritis were significantly lower than those in patients with bacterial infection (0.096±0.105 ng/mL vs. 4.94±13.763 ng/mL, p=0.001). However, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels showed no significant differences between the two groups. To assess the ability of PCT to discriminate between acute gouty arthritis and bacterial infection, the areas under the curves (AUCs) of serum PCT, uric acid, and CRP were 0.857 [95% confidence interval (CI), 0.798-0.917, p<0.001], 0.808 (95% CI, 0.738-0.878, p<0.001), and 0.638 (95% CI, 0.544-0.731, p=0.005), respectively. There were no significant differences in ESR and white blood cell counts between these two conditions. With a cut-off value of 0.095 ng/mL, the sums of sensitivity and specificity of PCT were the highest (81.0% and 80.6%, respectively). Serum PCT levels were significantly lower in patients with acute gouty attack than in patients with bacterial infection. Thus, serum PCT can be used as a useful serologic marker to differentiate between acute gouty arthritis and bacterial infections.